Numerical study on the bond between CFRP rod panels (CRPs) and concrete. (20th July 2018) - Jawdhari, Akram; Fam, Amir; Harik, Issam
Highlights: CFRP rod panel (CRP) is a promising retrofit system for concrete structures. Finite element models were developed to study the bond between CRP and concrete, and several parameters. A bilinear bond-slip model is proposed, with a maximum shear stress of 6.25 MPa and maximum slip ( δf ) of 0.45 mm. Decreasing rod diameter or increasing rod spacing/diameter ratio increases the ultimate strength. Debonding load of CRP is 51% higher than that of an externally bonded conventional CFRP plate with same FRP area. Abstract: In this study, finite element (FE) models are developed to examine the interfacial behavior of a new retrofitting system comprised small diameter carbon fiber reinforced polymer (CFRP) rods spaced apart a distance larger than the rod diameter. The CFRP rod panel (CRP) is adhesively bonded to the concrete surface. The study explores several key parameters, including bond-slip ( τ - δ ) relation, effective bond length, rod diameter ( D ), and rod spacing-to-diameter ( S / D ) ratio. The models were validated against previous double-lap CRP-concrete block tests. A bilinear ( τ - δ ) model that provides a good correlation to the failure loads of the entire range of specimens was established. The effective bond length was found for two commonly used CRPs, and was 85 mm for one with D  = 2 mm and S  = 6.35 mm, and 115 mm for that with D  = 4 mm and S  = 9.50 mm. A parametric study using 20 FE models was carried out, considering four rod dimeters (1–4 mm) and five S / D ratios (2.2–3.18). It was found that although debonding failure consistently governs; decreasing ( D ) or increasing ( S / D ) ratio increases the ultimate strength. The effect of ( S / D ) ratio is more pronounced for D = 1 mm than other diameters. The study also found that debonding load of CRP is 51% higher than that of an externally bonded conventional CFRP plate of similar cross-sectional area and mechanical properties.